The Influence of Corporate Social Responsibility (CSR), Company Size, and Sales Growth on Tax Avoidance - Ramadhani, Novi; Jamaluddin, Jamauddin (Indonesian Journal of Business Analytics, 2025)
This study aims to determine the influence of corporate social responsibility (CSR), company size, and sales growth on tax avoidance in food and beverage sub-sector companies listed on the Indonesia Stock Exchange from 2018 to 2022. The technique used was purposive sampling with a sample size that met the criteria of 26 companies. The type of data used is quantitative with secondary data sources from financial annual reports and corporate sustainability reports. This study uses the SPSS version 22 analysis tool. The test results show that corporate social responsibility (CSR) has a significant and negative impact on tax avoidance, and company size has a significant and positive impact on tax avoidance. Simultaneously, sales growth does not affect tax avoidance.